2007
DOI: 10.1038/sj.npp.1301411
|View full text |Cite
|
Sign up to set email alerts
|

5-HTTLPR Biases Amygdala Activity in Response to Masked Facial Expressions in Major Depression

Abstract: The amygdala is a key structure in a limbic circuit involved in the rapid and unconscious processing of facial emotions. Increased amygdala reactivity has been discussed in the context of major depression. Recent studies reported that amygdala activity during conscious emotion processing is modulated by a functional polymorphism in the serotonin transporter gene (5-HTTLPR) in healthy subjects. In the present study, amygdala reactivity to displays of emotional faces was measured by means of fMRI at 3T in 35 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
3
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 37 publications
8
108
3
3
Order By: Relevance
“…However, the second study found that the SS genotype or S allele was nonsignificantly associated with decreased risk of depression in the British population [140]. A nonsignificant protective effect of the S allele was observed among Spaniards [109] and Germans [141,142]. Five studies of whites [143][144][145][146][147] found no substantial relationships between the 5-HTTLPR genotype and major depressive disorder.…”
Section: Major Depressive Disorder and 5-httlpr Polymorphismmentioning
confidence: 99%
“…However, the second study found that the SS genotype or S allele was nonsignificantly associated with decreased risk of depression in the British population [140]. A nonsignificant protective effect of the S allele was observed among Spaniards [109] and Germans [141,142]. Five studies of whites [143][144][145][146][147] found no substantial relationships between the 5-HTTLPR genotype and major depressive disorder.…”
Section: Major Depressive Disorder and 5-httlpr Polymorphismmentioning
confidence: 99%
“…Interestingly, the serotonin system is related to emotion regulation, most likely through its effects on attentional control over negative stimuli; that is, many experimental studies show that 5-HT is implicated in enhanced sensitivity to negative stimuli and modulates the responsiveness of the amygdala via connected frontal regions (for reviews, see Cools, Roberts, & Robbins, 2007;Hariri & Holmes, 2006). Moreover, the amygdala response to negative stimuli is revealed to be associated with the above-mentioned polymorphism of 5-HT (e.g., Dannlowski et al, 2008). It has been proposed that the short allele variant, associated with a reduced 5-HT function, causes increased brain responses to negative stimuli (Bethea et al, 2004).…”
Section: Neurobiological Underpinnings Of Impaired Attentional Contromentioning
confidence: 99%
“…A replicated association has been found between amygdala reactivity to emotional stimuli and a polymorphism in the serotonin transporter gene (Hariri et al, 2002Pezawas et al, 2005), and other genes in the serotonergic pathway also seem to influence amygdala reactivity (Brown et al, 2005;Buckholtz et al, 2007;Dannlowski et al, 2007;Iidaka et al, 2005). tioning.…”
Section: Introductionmentioning
confidence: 99%